Training load and intensity in professional female cyclists during highly successful seasons - Roete, A.; van Erp, T.; Elferink-Gemser, M. T.; Kempe, M.; Lamberts, R. P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Training plays an essential role to be successful in professional cycling. However, insights into training and racing load in professional female cyclists are limited. Therefore, this study aims to describe and determine the differences in training or race load in female professional cyclists during highly successful versus less successful seasons. METHODS: Training and race data of professional female cyclists during 43 seasons, over a 7-year period were analyzed. Each season of a cyclist was classified as either highly successful or less successful, based on the mean number of ProCyclingStats points per race (*5: highly successful;; <5: less successful). Mean external (duration, distance, power output (PO), kilojoules (kJ), training stress score (TSS)), as well as mean internal (heart rate (HR), rating of perceived exertion (RPE) and Edwards Training Impuls (eTRIMP)) load was determined per session. In addition, PO distribution, as a percentage of time spend in each power zone, were calculated. A multilevel random intercept model followed by pairwise comparison was used to determine if differences existed between highly successful and less successful seasons, while significance was set at p<0.05. RESULTS: In total, 14 professional female cyclists were included in this study, resulting in 18 highly successful and 25 less successful seasons. Mean duration (2.6±0.2 vs 2.3±0.2, p<0.001, and 3.2±0.2 vs 3.0±0.2 h, p<0.01), distance (75±6 vs 66±5, p<0.001, and 116±7 vs 104±9 km, p<0.001) and relative kJ burnt (23.6±1.5 vs 20.4±2.3, p<0.001, and 31.9±2.0 vs 29.4±3.4 kJ?kg^-1, p<0.001) during training and race sessions, respectively, were higher during highly successful seasons, while no differences were found for mean PO or TSS. In line with this, no differences were found for internal load markers (HR, RPE, eTRIMP) during less and highly successful seasons, while session RPE (2022±191 vs 1725±198, p<0.01, 3076±288 vs 2718±322, p<0.01) were higher during the highly successful seasons. Intensity distribution analysis showed that cyclists, during highly successful seasons, spend relatively more time riding in PO zone 2 and less in PO zone 4 and 5 during training sessions (p<0.05), while they spend relatively less time in PO zone 5 and more in Zone 1 during races (p<0.01). CONCLUSION: Female professional cyclists, during highly successful seasons train longer and burn more kJ per session than cyclists during less successful seasons. In addition, when training they spent more time in PO zone 2 and less in zone 4 and 5. This finding likely highlights the importance of building up endurance capacity and fatigue resistance, which has shown to be an important factor for success in professional cycling(1,2). In line with training longer, cyclists during highly successful seasons were selected for longer, and generally more prestigious, cycling races than cyclists during less successful seasons.